Rabin Abraham (Sofer) Schreiber – med Sočo in Kvarnerjem - Podbersič, Renato (Edinost in dialog, 2025)
Based on archival sources and literature, the article deals with the life and activities of the renowned Rabbi and Professor Abraham Adolfo Schreiber (1897, Eger–1982, Jerusalem), a member of Orthodox Judaism, descended from the old Hungarian Orthodox rabbinical Sofer -Schreiber family. Members of this family are descendants of Rabbi Moses (Chatam) Sofer-Schreiber (1762, Frankfurt am Main–1839, Pressburg/Pozsony/Bratislava), also called Chatam Sofer, an influential Jewish scholar in the large and important Jewish community in Bratislava/Pozsony/Pressburg, then in Hungary. Abraham Schreiber was an excellently educated, good and prolific writer, and it was in Gorizia that he began to devote himself to the preparation of critical editions of the works of medieval Talmudists, specializing primarily in the High Medieval rabbi Menachem Meiri. Rabbi Schreiber was the last rabbi in Gorizia; in 1936 he left the city for Opatija, where he took care of the Orthodox faithful, together with neighbouring Rijeka (Fiume, Reka). When anti-Jewish legislation was passed in fascist Italy, he and his family emigrated to Palestine in 1939. Between 1948 and 1966, he lectured at a Jewish Theological Seminary in New York.
Keywords: Hungarian Jewry; Jewish community in Abbazia; Jewish community in Gorizia; judovska skupnost v Gorici; judovska skupnost v Opatiji; madžarsko judovstvo; Orthodox rabbi; ortodoksni rabin; rabbinical family Sofer-Schreiber; rabinska družina Sofer-Schreiber